Implications of English Communication Anxiety on Hospitality Management Students' Work Attitudes in the Hospitality Industry During Internship Programs - Raysa Apriana Firdaus; Nabila Ufaira; Noliana Oktavia; Feri Ferdian (Brilliant International Journal Of Management And Tourism, 2023)
Objectives - This study aims to analyze the effect of anxiety communicating in English on the work attitude of hospitality management students in the hospitality industry during the internship program. Methodology - A quantitative approach was used on 539 hotel management students who had carried out internships in the hotel industry based on a stratified random sampling technique. The sample size researchers took and managed to collect 76 respondents from hotel management students who had carried out internships in the hotel industry. Then the data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). Findings - The results of the study show that the influence of anxiety affects the work attitude of hospitality students while doing internships. Originality – The effect of anxiety in communicating using English makes findings to get various kinds of anxiety faced so that it becomes better learning when communication in English and reduces anxiety. The novelty in this study found that many students still had anxiety in communicating using English during their internships.